Communicating through Calamity: Rural and Urban Extension Professionals’ Communication during and after a Hurricane - Angela B. Lindsey; Sandra Anderson; Lauri M. Baker; Kevin W. Baker (Journal of International Agricultural and Extension Education, 2021)
The purpose of this study was to determine the role urban and rural community status plays in the communication of Universityof Florida Cooperative Extension faculty and staff during and after a disaster by identifying the extent to which technology was utilized, thecommunication messages conveyed, and organizational communication versus personal communication. The crisis used for understanding these efforts was Hurricane Irma in 2017. An online survey methodology was used to collect data from Extension personnel across Florida. Results indicate there are differences between how rural and urban Extension faculty and staff communicate during and after a hurricane. The internet was used to a great extent as a communication channel by both rural and urban Extension professionals, but how they used the internet differed. Urban audiences chose more personal mediums when communicating personally about the hurricane, while rural participants used more social media when communicating on personal channels. Implications for thisstudy are an increased need for templates and communication training for Extension personnel. Future research should focus on understanding crisis communication during times of power loss and examine the different roles played by Extension in rural and urban counties
Keywords: crisis communication; disasters; hurricanes; rural; urban; organizational communication